The effect of illegal lead processing on blood lead levels in children living in the mining area - Ćorac Aleksandar; Barać Nemanja; Bukumirić Zoran; Barać Milan; Milićević Saša; Vidović Milka M.; Mijović Milica; Hudomal Snežana; Joksimović Viktorija; Paut-Kusturica Milica; Ilić Danijela; Jović Jelena; et al. (Vojnosanitetski Pregled)
Backgraund/Aim. The northern part of Kosovo was one of the largest lead and zinc production industries in Europe. Special attention has been paid to the landfill sites of these metals remained after past industrial activities. The inhabitants of Roma camps in this area are collecting led waste they process by crushing and melting in their shacks in primitively organized working environments. Because of all the aforementioned it was necessary to examine the concentration of blood lead level (BLL) in the children aged less than 6 years inhabiting this area, especially taking care of blood analysis of children living in Roma camps. Methods. The study was conducted in the municipality of Leposavić, Province Kosovo and Metohija, Serbia. Totally 78 subjects participated in the study. All the subjects were divided into two groups: the group I consisting of 42 children who lived in the Romas camp, and the group II with 36 children from a city kindergarten. Based on the mathematical model WRPLOT we found out that both groups of patients were in the low risk zone for industrial contamination exposure. Blood analysis was done according to the protocol provided by ESA Lead Care. Results. The average age of participants in the study was 4.60 ± 1.63 years. The mean BBL in the children from the group 1 was 19.11 μg/dL and from the group 2 4.87 μg/dL. There was a statistically significant difference in the mean values of BBL between the groups (U = 39, p < 0.001). All of the children from the group 1 had BBL greater than 5 μg/dL in comparison to 38.9% of the children from the group 2 (χ2 = 35.75, p < 0.001). Conclusion. Although both groups were located outside the zone of direct spread of pollution, the results indicate high concentrations of lead in blood of all the examined children. The concentration was higher in the children who lived in the area in which illegal processing of lead waste took place. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. TR 37016]